2011
DOI: 10.1017/s175173111000234x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing palm oil with maize oil and Curcuma longa supplementation on the performance, carcass characteristics, meat quality and fatty acid profile of the perirenal fat and muscle of growing rabbits

Abstract: An experiment has been conducted to study the effects of the inclusion of plant oil in rabbit diets. This study was aimed at evaluating the beneficial effects of the inclusion of maize oil (MO), rich in unsaturated fatty acids (UFAs), compared to palm oil (PO) containing saturated fatty acids (SFAs), on the meat fatty acid (FA) profile. As UFAs are susceptible to rancidity, Curcuma longa (CL), which is known for its antioxidant properties, was also added (3 g/kg) to the diet with two plant oils. CL contains cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
4
17
0
Order By: Relevance
“…In fact, Dalle Zotte (2002) reported an n-6/n-3 ratio of 11.6 for the rabbit hind leg, and Liu et al (2009) reported even higher values (around 14.6) for this ratio. Peiretti et al (2011b) found an n-6/n-3 ratio of 13.1 for the LD muscle of rabbits fed maize oil supplement diet, although values ranging from 1.1 to 1.9 for this ratio were found in the LD muscle of rabbits fed golden flaxseedsupplemented diets (Peiretti and Meineri, 2010). Moreover, in a trial using tomato by-products, Peiretti et al (2013) found similar values to those of the present study.…”
Section: Tbars Assaysupporting
confidence: 81%
“…In fact, Dalle Zotte (2002) reported an n-6/n-3 ratio of 11.6 for the rabbit hind leg, and Liu et al (2009) reported even higher values (around 14.6) for this ratio. Peiretti et al (2011b) found an n-6/n-3 ratio of 13.1 for the LD muscle of rabbits fed maize oil supplement diet, although values ranging from 1.1 to 1.9 for this ratio were found in the LD muscle of rabbits fed golden flaxseedsupplemented diets (Peiretti and Meineri, 2010). Moreover, in a trial using tomato by-products, Peiretti et al (2013) found similar values to those of the present study.…”
Section: Tbars Assaysupporting
confidence: 81%
“…The differences in the oil groups pertaining the muscle FA (Peiretti et al, 2011) are summarized in Table 2 on the basis of the univariate model. The maize oil decreased the palmitic (-12%) and oleic acids (-19%) and increased linoleic acid (+50%), while C increased the linolenic acid contents by 19%.…”
Section: Resultsmentioning
confidence: 99%
“…The animals were housed individually under standard conditions at a temperature of 22±2°C in wire cages at a height of 90 cm from the concrete floor. Four diets, which were reported in Peiretti et al (2011) were administered: iso-nitrogenous (187 g crude protein/kg dry matter (DM)), iso-ethereal (59 g ether extract/kg DM), iso-energetic (12 MJ digestible energy/kg DM), and aniso-unsaturated formulated with 4% maize oil (M, more unsaturated) and 4% palm oil (P, more saturated), without (No C) or with 3 g/kg C. longa supplementation (C). The experimental period lasted 30 d, with a previous 14 d adaptation period.…”
Section: Animals and Samplingmentioning
confidence: 99%
See 2 more Smart Citations